In search of deep faith : a pilgrimage into the beauty, goodness, and heart of Christianity - Belcher, Jim, 1965- (Downers Grove, Illinois : IVP Books, an imprint of InterVarsity Press, 2013)
"Grappling with [questions about faith and meaning], Jim Belcher set out on a quest to see how the Christian faith faces the challenges of the modern world and answers the cries of the human soul. Seeking renewal after a draining season of life, he and his family spent a year traveling through Europe, exploring the faith that has shaped civilizations throughout the centuries"--Amazon.com.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Christian pilgrims and pilgrimages -- Europe; Christian pilgrims and pilgrimages -- England -- Oxford; Voyages and travels -- Religious aspects -- Christianity; RELIGION / Holidays / Christian; Electronic books